2014
DOI: 10.3346/jkms.2014.29.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Acute Hepatitis A in Korea: A Nationwide Multicenter Study

Abstract: The aim of this study was to investigate the clinical characteristics of acute hepatitis A during a recent outbreak in Korea. Data of patients diagnosed with acute hepatitis A from 2007 to 2009 were collected from 21 tertiary hospitals retrospectively. Their demographic, clinical, and serological characteristics and their clinical outcomes were analyzed. A total of 4,218 patients (mean age 33.3 yr) were included. The median duration of admission was 9 days. The mean of the highest ALT level was 2,963 IU/L, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Recent reports indicated that outbreaks of HAV, with the subgenotype shifting from IA to IIIA, occurred from 2007 in South Korea, a neighboring country . The identification of subgenotype IIIA HAV homologous to Korean IIIA HAV from two patients (A8 and A9) in the present study, who had never been to South Korea, suggests that Korean IIIA HAV has been indigenized in Japan, and is most likely distributed widely in this country.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Recent reports indicated that outbreaks of HAV, with the subgenotype shifting from IA to IIIA, occurred from 2007 in South Korea, a neighboring country . The identification of subgenotype IIIA HAV homologous to Korean IIIA HAV from two patients (A8 and A9) in the present study, who had never been to South Korea, suggests that Korean IIIA HAV has been indigenized in Japan, and is most likely distributed widely in this country.…”
Section: Discussionsupporting
confidence: 50%
“…HA13‐2175 and HA13‐2176 were 100% identical to each other and shared 98.7% similarity with a Korean strain (JQ655151). However, patients A8 and A9 had no history of travel to South Korea, where outbreaks of HAV, with an increasing prevalence of subgenotype IIIA over time, have been reported since 2007 …”
Section: Resultsmentioning
confidence: 99%
“…[8, 9] The seroepidemiologic shift resulted in a great national outbreak of hepatitis A that peaked in 2009. [10, 11] The age and area-adjusted overall seroprevalence rates of anti-HAV from 2010 to 2014 was lower than those from 2005 to 2009. This resulted from the marked decrease of seroprevalence in persons aged 30 to 49 years throughout the 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of hepatitis A increased in persons with chronic liver disease or old age. [11, 19, 20] Taking this changing seroprevalence into account, more severe clinical presentations in older patients and subsequent rise in morbidity and mortality can be expected in the near future. The mortality rate of acute hepatitis A was reported to be 0.47%, and acute renal failure developed in 2.7% of hepatitis A cases during the outbreak in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation